PENGARUH PENERAPAN PERMAINAN BOLING RUN TERHADAP KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 1 KOTA PEKANBARU - Silamarzela '; Ria Novianti; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to study the effect of boling run game implementation on rough motor ability of 4-5 years old child. This research was conducted at kindergarden 1 Pekanbaru City during May 2017. The research used experimental method with one group pre-test post-test design design with 18 samples. The type of instrument used in this study is to use an observation sheet to record about the activities that occurred during the given treatment. Based on the result of hypothesis test, there is influence of boling run game implementation on gross motor ability of children aged 4-5 years in TK Negeri Pembina 1 Kota Pekanbaru. Obtained a tcount of 72.412 with sig 0.000, because sig <0.05 it can be concluded that there is influence of applying boling run against gross motor abilities in children. In Hypothesis test can be seen tct = 72,412> ttabel = 2,110. It can be interpreted that there is a significant influence on the implementation of bowling run game against rough motor skills in children age 4-5 years in kindergarden 1 Pekanbaru City of 91.39%.Keywords: Rough Motoric, Run Boling Games